Design of Programmable Logic Controller (PLC) on Smart Fertilizer Distribution System - Nike Dwi Grevika Dranatantiyas; Annisa Herliana; Ahmad Suaif; Zunanik Mufidah (Jurnal Multidisiplin Madani, 2023)
The control system in agriculture is an important study to regulate the application of fertilizers to plants. The control system can use PLC control system which has good system robustness and easy program language. The purpose of this research is to design a simulated fertilizer irrigation system based on a programmable logic controller (PLC) system. The PLC program used is CX-program and the simulator circuit uses Fluidsim simulator. The system components used are the main reservoir, pump, solenoid valve, valve, level sensor, and light indicator. The system is organized by dividing inputs and outputs that are directly integrated into the PLC system. The components are arranged using fluidsim and the PLC control system using CX-Programmer using ladder logic language. The control system integration and system circuitry are connected using KeepServerEX. The output of this system is a successful operation function and a digital system response to the time of the system. From the results of the system response provides a fairly good timeliness so that this irrigation system can be considered in the implementation of fertilizer delivery system